Pensamiento científico en la primera infancia: percepciones y prácticas de educadoras de párvulos en Chile - Gutiérrez Gálvez, Tabita (2026)
Scientific education in early childhood fosters the development of critical thinking, curiosity, and inquiry skills in young children. However, several studies warn that its implementation in early childhood education faces obstacles related to teacher training, available resources, and adult beliefs that limit autonomous exploration. Considering this context, the aim of this study was to characterize the perceptions and methodological strategies employed by early childhood educators working with middle-level groups to promote the development of scientific thinking in young children. A mixed-methods approach with a qualitative predominance was used, based on semi-structured interviews and a questionnaire administered to educators in the province of Arauco. The results reveal five key areas: a general yet emerging understanding of scientific thinking; challenges associated with children’s verbal expression, limited resources, and insufficient professional preparation; mediation practices centered on guiding questions, sensory exploration, and simple experiments, among others. The study concludes that, although educators recognize the importance of this skill, they require more systematic training and stronger institutional support to enhance scientific inquiry experiences from an early age.